Vinculação dos conceitos do teste grocery shelving task com a CIF em pacientes submetidas a cirurgia para o tratamento do câncer de mama - Silva, Conceição Aparecida Vitoriano Souza (2020)
Background: Technological advances for the treatment of breast cancer have allowed an increase in survival, and in contrast, functional sequelae, making it necessary to have a global view of the impact on functional capacity and functional performance, which is why the proposal to link the Grocery Shelving Task test and the International Classification of Disability, Functionality and Health. Objective: Link the concepts measured by the GST Test with CIF codes and qualifiers. Method: The linking process followed the 10 rules proposed by Cieza, et al., And was carried out using the model of extraction and identification of the concepts that were found in the GST test. After the calculation that compared the pre and postoperative time, a parallel was made between the ICF qualifiers and the GST test. Results: The GST test linking process included five components of Activity and participation “d” (d4103 sitting, d4104 getting up, d450 walking, d430 getting up and carrying objects, and for rule “9” the code d440 Fine use of the hand), and two of Body functions (b4100 FC and b4408 Respiratory functions, others specified). The ICF qualifiers allowed to identify the functional impairment resulting from the surgical procedure, observing: .0 (no problem) = 25.5%, .1 (mild problem) = 57.4%, .2 (moderate problem) = 8. 5%, .3 (Serious problem) = 8.5%. Conclusion: The link with the ICF allowed to identify and classify codes related to the activity and participation component, while the qualifiers allowed to grade the observed problems. Most women presented functional impairments resulting from the surgical procedure, even if mild.